Fibrosing Mediastinitis: Successful Stenting of the Pulmonary Artery - Rennae Thiessen; Fred Matzinger; Jean Seely; Rima Aina; Peter MacLeod (Canadian Respiratory Journal)
Fibrosing mediastinitis is a rare benign condition, which can cause compression of the pulmonary or systemic vessels, tracheobronchial tree, coronary arteries or esophagus, leading to disabling clinical symptoms and even death. The case of a 26-year-old woman who presented with dyspnea is described. She was found to have 80% stenosis of the right pulmonary artery secondary to fibrosing mediastinitis. The stenosis was managed successfully with an endovascular Palmaz-Schatz stent, and the patient remains symptom-free 10 years later.